Change in the deformation mode resulting from beta-omega compositional partitioning in a TiMo alloy: Room versus elevated temperature. (15th March 2017) - Mantri, S.A.; Choudhuri, D.; Alam, T.; Ageh, V.; Sun, F.; Prima, F.; Banerjee, R.
Abstract: The effect of beta-omega compositional partitioning, introduced via isothermal annealing, on the deformation behavior of a TiMo alloy was investigated via tensile testing at room and elevated temperatures. While beta with compositionally congruent athermal omega precipitates primarily exhibits twinning, after beta-omega compositional partitioning the same alloy deforms via slip. This change in deformation mode can be rationalized based on the solute content within the beta matrix, with reference to the Bo-Md plot. Tensile testing at elevated temperatures revealed that both conditions deformed via slip while exhibiting serrated flow. Graphical abstract: